2004
DOI: 10.1620/tjem.203.349
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Hypoxanthine Levels in Nonpreeclamptic Twin Pregnancies

Abstract: We have observed that the elevated plasma adenosine levels are associated with hyperuricemia in nonpreeclamptic twin pregnancies. In animal models, extracellular adenosine is taken up by cells to form adenine nucleotides or is degraded to other purine metabolites such as hypoxanthine, which is further metabolized to xanthine and uric acid. In this study, we measured plasma hypoxanthine levels to evaluate the role of adenosine in hyperuricemia among women with twin pregnancies. Maternal blood samples were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In fact, high levels of IL-10 were observed in pregnant mice in this study. On the other hand, maternal metabolism, such as glucose, lipid [ 54 , 55 ], and purine metabolism [ 56 ], changes significantly during pregnancy considering that the alteration in host nutrient conditions may be associated with an enhancement of parasite-growth during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high levels of IL-10 were observed in pregnant mice in this study. On the other hand, maternal metabolism, such as glucose, lipid [ 54 , 55 ], and purine metabolism [ 56 ], changes significantly during pregnancy considering that the alteration in host nutrient conditions may be associated with an enhancement of parasite-growth during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study by Fischer et al [5], a 24-h urine collection was performed, and the higher maternal serum uric acid levels were demonstrated to result from increased uric acid production, as reflected in the increased daily uric acid excretion in twin pregnancies. In addition, our previous reports suggested that increased plasma adenosine is the main factor contributing to hyperuricemia in women with twin pregnancies [4,15]. Adenosine is a precursor for synthesis of adenosine triphosphate, and is a potent vasodilator and a metabolic regulator in the cardiovascular system [16].…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancy, serum uric acid concentrations decrease during the first trimester by at least 25%, and return to normal levels between the second and third trimester of pregnancy [17]. It has been shown that maternal serum uric acid concentrations rise in multiple pregnancies [18][19][20][21], suggesting that the presence of fetus and/or placenta contributes to the increased production of uric acid. Preeclampsia is a pregnancy-specific disease, characterized by hypertension and proteinuria, which contributes substantially to the incidence of iatrogenic preterm deliveries with its sequelae.…”
Section: Introductionmentioning
confidence: 99%